2020
DOI: 10.1177/0040517520932557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of knitting structure and yarn composition on thermal comfort properties of bi-layer knitted fabrics

Abstract: In this work, nine bi-layer knitted samples with varied knitting structures and made up of different yarn compositions were fabricated, and their thermal comfort properties were investigated. The thermal comfort properties were evaluated by breathability, water transfer properties, thermo-physiology properties and dynamic cooling properties, and their relationship with fabric knitting structure and yarn composition were investigated statistically. It was observed that bi-layer knitted fabrics with meshes at on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…The use of different material arrangements in sleeping bags has increased in recent years, allowing them to be used in a variety of conditions while maintaining comfort. The use of the most modern textile science and technology in the production of this type of materials is developing every day [ 12 , 13 , 14 ]. Winter sleeping bags must provide adequate thermal insulation, as well as protection against weather conditions, while summer sleeping bags must—oppositely—provide lower thermal insulation; therefore, different composition of raw materials should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…The use of different material arrangements in sleeping bags has increased in recent years, allowing them to be used in a variety of conditions while maintaining comfort. The use of the most modern textile science and technology in the production of this type of materials is developing every day [ 12 , 13 , 14 ]. Winter sleeping bags must provide adequate thermal insulation, as well as protection against weather conditions, while summer sleeping bags must—oppositely—provide lower thermal insulation; therefore, different composition of raw materials should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Mbise et al found that the hydrostatic pressure difference between the two layers of spacer fabric is one of the factors affecting moisture transfer [8]. A studies on the effect of yarn composition and knitting structure on bi-layer knitted fabrics [36]; a comparative study of eri-silk, wool, and bamboo knitted fabrics [37]; and a study of 100% eri-silk for active sportswear applications [38] have previously been conducted. The air permeability, water vapor permeability, thermal conductivity, wicking, and drying ability of bi-layer knitted fabric made up of polypropylene as the inner layer and modal as the outer layer with one tuck point of repeat were found to be higher when compared to other bi-layer, plated, and single jersey structures [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fabrics with many large pores breathe better than fabrics with few and small holes. 16 The thermal physiological properties are defined as wearing comfort in terms of thermal and moisture transfer effects, which can be assessed by thermal resistance and water vapor resistance. 17 Water vapor resistance has been described as the ability of clothing to allow the transmission of moisture vapor by diffusion, depending on air permeability.…”
mentioning
confidence: 99%
“…For example, bilayer knitted fabrics, in which the inner face made up of polypropylene or polyester filament has good capillary action and the outer face made from a hydrophilic yarn allows high absorption, have a better moisture management property to achieve a high level of clothing comfort. 16,22…”
mentioning
confidence: 99%